Films from Countries in Crisis and Switzerland: The New Argentine Cinema, Greek New Wave and Swiss Film Institutions - Konstantinos Tzouflas (Cinergie, 2022)
This paper will explore the relationship between Swiss film institutions and cinematic New Waves that appear in countries which were or are in crisis. To this end, it will compare how the New Argentine Cinema (NAC) and Greek New Wave (GNW) were received at the Locarno Film Festival, the Fribourg Film Festival and the Visions sud est Fund (case studies). Argentina’s wave emerged just before the country’s default in 2001, while the Greek wave arose at the same time as the sovereign-debt crisis in Greece in 2009. Switzerland plays a role in their success, since it has always maintained a rich cinematic culture with historic festivals and producers, as well as government agencies and foundations assisting filmmakers from (semi-)peripheral countries. The first aim of this paper is to (i) investigate how the NAC and GNW were received at the Locarno and Fribourg festivals. By analysing the material in their official programmes, it will (ii) determine whether there is a proliferation of crisis-related terms in the way these waves are presented. Finally, this paper will (iii) expound on their support by Visions sud est Fund and other Swiss institutions and assess the impact of Swiss funding on the NAC and GNW.